Electrostatic phase separation: a review - Mhatre, S.; Vivacqua, V.; Ghadiri, M.; Abdullah, A.M.; Al-Marri, M.J.; Hassanpour, A.; Hewakandamby, Buddhika N.; Azzopardi, Barry J.; Kermani, B. (Elsevier, 2015)
The current understanding and developments in the electrostatic phase separation are reviewed. The literature covers predominantly two immiscible and inter-dispersed liquids following the last review on the topic some 15 years. Electrocoalescence kinetics and governing parameters, such as the applied field, liquid properties, drop shape and flow, are considered. The unfavorable effects, such as chain formation and partial coalescence, are discussed in detail. Moreover, the prospects of microfluidics platforms, non-uniform fields, coalescence on the dielectric surfaces to enhance the electrocoalescence rate are also considered. In addition to the electrocoalescence in water-in-oil emulsions the research in oil-in-oil coalescence is also discussed. Finally the studies in electrocoalescer development and commercial devices are also surveyed.